THE PRIORITY WAYS OF IMPROVEMENT OF THE RULE-MAKING ACTIVITY IN THE CONTEXT OF PROVIDING EFFECTIVE LEGAL POLICY IN THE REPUBLIC OF BELARUS - Ipatov, Вадим Дмитриевич (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2017)
The subject of research is the public relations in the field of planning, forecasting and other phases of the rulemaking. The aim is to determine the priority ways of standards-related activities development, the formation and implementation of effective legal policy in the Republic of Belarus. The trends of the current stage of legal policy development in the Republic of Belarus are analyzed in the article: searching for new criteria for the system of law and legislative system formation, legal system in the context of the world economy globalization, global and regional integration processes. The convergence of national legislation with the legislation of other countries within the participation of the Republic of Belarus in international organizations and interstate formations is called the one of the legal development priorities. Special attention, according to the author, should be given to the implementation of international commitments undertaken in the framework of the Eurasian Economic Union. The analysis is resulted in a ways justification for further development of rulemaking institutes of strategic and operational planning, in public discussion of draft regulations, in impact assessment of the adoption (publication) of the normative legal act, in legal monitoring. The author relates the solution to these problems with a new draft law of the Republic of Belarus “On normative legal acts of the Republic of Belarus”, prepared by the National Centre of Legislation and Legal Research of the Republic of Belarus on the basis of provisions systematization of the current Law and Rules for preparation of draft regulations, and passed by the House of Representatives of the National Assembly of the Republic of Belarus in the first reading.